2006
DOI: 10.1111/j.1552-6569.2006.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variability in the Detection of Cerebral Emboli with Transcranial Doppler During Cardiac Surgery

Abstract: Using intensity thresholds higher than the optimal for embolus detection decreases HITS counts. Choosing a threshold depends on the type of method used for measuring the signal intensity. Uniform threshold criteria and comparative studies between different Doppler devices are necessary for making clinical trials more comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…5,8,9,13 Some studies have found that patients undergoing CABG with higher HITS counts were more likely to experience cognitive deficits 1,2,5,6 or higher rates of frontal lobe dysfunction, 16 but others have found that there is no correlation between HITS counts and neurological symptoms or cognitive deficits. 6,8,17 Several methodological issues may account for the variability among these studies, including small sample sizes, 1,6 differences in intensity thresholds used to detect HITS, 13 artery location (carotid versus middle cerebral artery), 1,8,12 unilateral or bilateral recordings, 2,8,12 type of ultrasound device, 13,18 quality of TCD recordings, 18 inconsistency of signal reviewing techniques (automatic versus manual), 13,18 and the effects of several confounding variables such as the duration of CPB and core body temperature. 2 We sought to overcome these limitations by studying a large number of low-risk patients undergoing †HITS were recorded unilaterally in the left common carotid artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,8,9,13 Some studies have found that patients undergoing CABG with higher HITS counts were more likely to experience cognitive deficits 1,2,5,6 or higher rates of frontal lobe dysfunction, 16 but others have found that there is no correlation between HITS counts and neurological symptoms or cognitive deficits. 6,8,17 Several methodological issues may account for the variability among these studies, including small sample sizes, 1,6 differences in intensity thresholds used to detect HITS, 13 artery location (carotid versus middle cerebral artery), 1,8,12 unilateral or bilateral recordings, 2,8,12 type of ultrasound device, 13,18 quality of TCD recordings, 18 inconsistency of signal reviewing techniques (automatic versus manual), 13,18 and the effects of several confounding variables such as the duration of CPB and core body temperature. 2 We sought to overcome these limitations by studying a large number of low-risk patients undergoing †HITS were recorded unilaterally in the left common carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…who was unaware of the results of the cognitive assessment and patient treatment allocation reviewed the TCD recordings and classified ultrasonic signals into true or equivocal HITS, Doppler speckles, and artifacts according to preestablished criteria. 13 Only true HITS were considered in the final counts of HITS. The quality of the TCD recording was assessed using a 5-point scoring scale.…”
Section: Tcd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial Doppler (TCD) has been used to detect emboli in the cerebral circulation during cardiopulmonary bypass (CPB) and cardiac surgery through the identification of high‐intensity transient signals or HITS 1,2 . Despite the wide use of TCD for embolus detection, accurate differentiation of solid from air emboli with this technology has not been achieved 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Such physiological inference can be obtained by transcranial Doppler (TCD) examination, 12 and by measurements of inhibition of platelet-induced aggregation. 13,14 Previous studies 12,15 have documented that TCD can reliably and noninvasively detect and quantify emboli in the cerebral circulation, by recognizing brief transient increases in the intensity of the ultrasound signal designated as microembolic signals (MES), which indicate the presence of air or solid emboli in the cerebral circulation. Similarly, several tests of platelet function have been used to evaluate the efficacy and safety of a combined therapy based on aspirin and oral anticoagulants.…”
mentioning
confidence: 99%